Archaeological Information and Geographical Information Systems in the context of Spatial Planning - Rocha, Leonor (2013)
European regional/spatial planning Charter (DGOT, 1988: 9), approved in 1984 by the Council of Europe, states that spatial planning "gives geographical expression to the economic, social, cultural and ecological policies of society. It is at the same time a scientific discipline, an administrative technique and a policy developed as an interdisciplinary and comprehensive approach directed towards a balanced regional development and the physical organisation of space according to an overall strategy." This document contains the guiding principals for spatial planning at its core, henceforth understood to be the implementation of public policy which is designed to be interdisciplinary and to improve people's quality of life and well-being.